2022
DOI: 10.1186/s12888-022-04195-5
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of a screening protocol for antenatal depression (SPADe) in Blantyre District, Malawi

Abstract: Background Depression is one of the most common perinatal mental health problems that affect pregnant women. Antenatal depression can adversely affect the well-being of the pregnant woman and her foetus. Depression is rarely detected by midwives due to the unavailability of relevant screening instruments in Malawi. A Screening Protocol for Antenatal Depression (SPADe) was developed and recommended for possible use to screen for depression in antenatal clinics in the country. The acceptability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Considering that perinatal adolescents are at high risk of common mental health problems, such as depression and anxiety, integrating screening of common perinatal mental health problems into routine antenatal clinics can help improve detection. Although it may be argued that doing this may increase the workload of the healthcare workers, a recent study (Chorwe-Sungani et al, 2022a) found that it is feasible and acceptable to implement a Screening Protocol for Antenatal Depression (SPADe), delivered by midwives, in routine antenatal clinics in Malawi, especially if the screening tools are brief. In addition, providing information about mental health during routine antenatal clinics may destigmatise perinatal common mental health problems, thereby encouraging help-seeking.…”
Section: Conclusion and Practice Implicationsmentioning
confidence: 99%
“…Considering that perinatal adolescents are at high risk of common mental health problems, such as depression and anxiety, integrating screening of common perinatal mental health problems into routine antenatal clinics can help improve detection. Although it may be argued that doing this may increase the workload of the healthcare workers, a recent study (Chorwe-Sungani et al, 2022a) found that it is feasible and acceptable to implement a Screening Protocol for Antenatal Depression (SPADe), delivered by midwives, in routine antenatal clinics in Malawi, especially if the screening tools are brief. In addition, providing information about mental health during routine antenatal clinics may destigmatise perinatal common mental health problems, thereby encouraging help-seeking.…”
Section: Conclusion and Practice Implicationsmentioning
confidence: 99%
“…Country Example: In Blantyre district, Malawi, it is estimated that 19% of women attending antenatal care services are suffering from antenatal depression ( 26 ). A further investigation demonstrated that introducing antenatal screening by midwives for maternal depression would be feasible to midwives working in this setting ( 27 ). The barrier to introducing screening was lack of a locally relevant screening tool, so the Screening Protocol for Prenatal Depression (SPADe) was developed, which was acceptable to surveyed midwives ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…A further investigation demonstrated that introducing antenatal screening by midwives for maternal depression would be feasible to midwives working in this setting ( 27 ). The barrier to introducing screening was lack of a locally relevant screening tool, so the Screening Protocol for Prenatal Depression (SPADe) was developed, which was acceptable to surveyed midwives ( 27 ). However, mental health services in Malawi are underfunded and with limited or no access from antenatal clinics, so the team felt it was unethical to introduce the screening without effective treatment ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations